Hox genes: methods and protocols - Graba, Yacine; Rezsohazy, René (Methods in molecular biology, 2014)
"Hox genes: methods and protocols explores techniques and methodologies which arose from or were successfully applied to the study of Hox genes and Hox proteins, at the intersection of experimental embryology, genetics, biochemistry, physiology, evolutionary biology, and other life sciences. This detailed volume begins with a section on discovery and functional analysis of Hox genes, and then it continues onward to discuss mode of action and biomedical applications of Hox proteins. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls